Improving Learning Outcomes of Inner Foot Passing Technique in Football Games Through the Pair Playing Method in Class VII Students of SMP Negeri 14 Central Bengkulu - Akabar, A. (Journal Of Dehasen Educational Review, 2023)
This study aims to determine the results of learning the passing of the inner foot in a soccer game through the pair playing method. In this game it is limited to the inner foot passing technique. The method used is classroom action research.The subjects of this study were students of class VII SMP Negeri 14 of Central Bengkulu with a total of 17 students. The sequence of research activities includes:1) planning, 2) implementation, 3) observation, 4) reflection. The data collection used RPP, observation sheets and documentation. The data analysis used a percentage description. The results showed that in the first cycle the average passing skill of the inner foot was 56, students who scored above 75 (KKM) were 7 students or 56%. Whereas in the second cycle the average of the inner foot passing skills was 78, students who scored above 75 were 13 students or 78%. So that it has met the target, which is 75%. The results showed an increase in student activeness, sincerity and courage of students in participating in learning. The pleasant atmosphere of student learning also motivates students to take lessons.